Jet flow and noise predictions for the Doak laboratory experiment - Gryazev, Vasily; Markesteijn, Annabel P.; Karabasov, Sergey A.; Lawrence, Jack L. T.; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Large-eddy simulations (LESs) are performed for two isolated unheated jet flows corresponding to a Doak Laboratory experiment performed at the University of Southampton. The jet speeds studied correspond to acoustic Mach numbers of 0.6 and 0.8 as well as Reynolds numbers based on the nozzle exit diameter of about one million. The LES method is based on the compact accurately boundary-adjusting high-resolution technique (CABARET) and is implemented on graphics processing units (GPUs) to obtain 1000–1100 convective time units for statistical averaging with reasonable run times. In comparison with the previous jet LES calculations with the GPU CABARET method, the mean-flow velocity and turbulent intensity profiles are matched with the hot-wire measurements just downstream of the nozzle exit. The far-field noise spectra of the Doak jets are evaluated using two methods: the Ffowcs Williams–Hawkings approach and a reduced-order implementation of the Goldstein generalized acoustic analogy. The flow and noise results are compared with hot-wire and acoustic microphone measurements of the Doak Laboratory and critically analyzed in comparison with the NASA small hot jet acoustic rig database.